Peningkatan Kapasitas Pelaku UMKM Dalam Perencanaan Keuangan dan Manajemen Arus Kas Gerakan Pemuda Ansor di Pagedangan Tangerang - Destian Andhani; Nur Rachmah Wahidah; Asep Muhammad Lutfi (Jurnal PKM Manajemen Bisnis, 2026)
This community service program aimed to enhance the financial planning and cash flow management capabilities of Micro, Small, and Medium Enterprises (MSMEs) in Pagedangan, Tangerang. The program addressed key challenges faced by MSME owners, including limited understanding of financial planning, inadequate cash flow management skills, and weak financial analysis capabilities. Conducted over a two-day period, the program involved 32 MSME participants and employed various learning methods, including lectures, group discussions, case studies, demonstrations, and hands-on practice. The evaluation results indicated substantial improvements in participants’ financial knowledge and skills. The average knowledge score increased from 52.8 in the pre-test to 84.3 in the post-test, representing a 59.7% improvement. In terms of practical competencies, 100% of participants successfully developed a financial recording format, 81.3% were able to prepare cash flow projections, 93.8% successfully calculated the Break-Even Point (BEP), and 84.4% were capable of preparing a simple profit-and-loss statement. Participant satisfaction reached 93.8%, while all participants expressed commitment to implementing the financial management systems introduced during the program. The findings demonstrate that the program significantly improved the financial literacy and financial management capacity of participating MSMEs, thereby increasing their potential access to financing opportunities. To ensure long-term sustainability and maximize impact, continuous mentoring and follow-up assistance are recommended.